How to outfox your friends when you don't have a clue - Keating, Jess (Sourcebooks Jabberwocky, 2015)
As her thirteenth birthday nears, Ana is very happily making a behind-the-scenes documentary at the zoo her parents run and delighted that her best friend, Liv, is visiting from New Zealand, but things start to fall apart when she brings her old and new friends together.